Effect of Addition of Coconut Shell Charcoal Ash to Clay Soil on Compaction Test Results - Brigita Suzanna; Irwan Lie Keng Wong; Monika Datu Mirring Palinggi (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The purpose of this research is to determine the physical properties of clay soil and to analyze the effect of adding coconut shell charcoal ash to the clay soil. The soil samples used in this study came from Tanralili District, Maros Regency, two sample points were taken and the variations in the levels of addition of coconut shell charcoal ash is 0%, 4%, 6%, 8%, 10%. The test method used refers to ASTM (American Society for Testing Materials). The tests carried out were testing the physical properties of the soil in the form of moisture content, specific gravity, Atterberg boundaries, filter analysis, and hydrometer analysis, then a compaction test was carried out to determine the maximum soil density. The results of the test obtained a moisture content value of 28.811%, a specific gravity of 2.58 g / cm3 so that it is classified as organic clay. As well as the plasticity index value of 9.926% with moderate plasticity from the 7% -17% interval. Then from the test results of soil compaction testing with the addition of coconut shell ash, the dry density (gdry) equal to 0.862, 0.886, 0.914, 0.943, 0.962, this means that the soil sample experienced an increase in dry density (gdry) of 11.60%. From the research results it can be concluded that the addition of coconut shell charcoal ash can increase the value of soil dry density so that it can be used to increase the value of the carrying capacity of clay soil.